Statistical optimization of process parameters for threshold voltage in 22 nm p-Type MOSFET using Taguchi method - Maheran A.H.A.; Menon P.S.; Shaari S.; Ahmad I.; Faizah Z.A.N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electron beam lithography; Field effect transistors; Metals; MOS devices; Nanoelectronics; Oxide semiconductors; Reconfigurable hardware; Signal to noise ratio; Silicides; Taguchi methods; Threshold voltage; Titanium dioxide; 22 nm; Compensation implantations; High-k/metal gates; International Technology Roadmap for Semiconductors; L9 orthogonal arrays; PMOS; Process parameter variations; Statistical optimization; MOSFET devices